An Art-Historical Analysis of Selected Sacred Sufi Paintings in Kano, Nigeria - Nadir A. Nasidi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2023)
‘Iconoclasm’, which may simply be defined as the destruction of artworks as a result of hatred towards them is a common phenomenon in all the three major Abrahamic desert religions; Judaism, Christianity and Islam. Because Islam frowns at representational art, especially sculptures in the round, many Muslim artists pursue and develop their creativity in the elegant Arabic calligraphic embellishments used to adorn the walls of mosques, palaces and the covers of Islamic books. However, despite the growing nature of iconoclasm amongst mainstream Muslims, the Sufis see no harm in visually and artistically representing their saints and hermits as a way to honour them and seek their barakah (blessings). It is on this basis that this paper examines selected sacred Sufi paintings of Kano, Nigeria. Relying heavily on oral interviews and written sources this paper traces the historical development of sacred Sufi paintings in Kano, Nigeria, focusing largely on the art historical appreciation and contextualization of such paintings. The paper also found out that despite the importance of sacred Sufi paintings in the reconstruction of history, they receive little or no scholarly attention.